Sugar-sweetened beverage consumption, correlates and interventions among Australian Aboriginal and Torres Strait Islander communities: a scoping review protocol. Issue 7 (31st July 2017) - Avery, Jodie C; Bowden, Jacqueline A; Dono, Joanne; Gibson, Odette R; Brownbill, Aimee; Keech, Wendy; Roder, David; Miller, Caroline L
Abstract : Introduction: Aboriginal and Torres Strait Islander communities of Australia experience poorer health outcomes in the areas of overweight and obesity, diabetes and cardiovascular disease. Contributing to this burden of disease in the Australian community generally and in Aboriginal and Torres Strait Islander communities, is the consumption of sugar-sweetened beverages (SSBs). We have described a protocol for a review to systematically scope articles that document use of SSBs and interventions to reduce their consumption with Aboriginal and Torres Strait Islander people. These results will inform future work that investigates interventions aimed at reducing harm associated with SSB consumption. Methods and analysis: This scoping review draws on a methodology that uses a six-step approach to search databases including PubMed, SCOPUS, CINAHL, Informit (including Informit: Indigenous Peoples), Joanna Briggs Institute EBP Database and Mura, between January 1980 and February 2017. Two reviewers will be engaged to search for and screen studies independently, using formulated selection criteria, for inclusion in our review. We will include primary research studies, systematic reviews including meta-analysis or meta-synthesis, reports and unpublished grey literature. Results will be entered into a table identifying study details and characteristics, summarised using a Preferred Reporting Items for Systematic Reviews and Meta-Analysis chart and then critically analysed. Ethics and dissemination: This review will not require ethics committee review. Results will be disseminated at appropriate scientific meetings, as well as through the Aboriginal and Torres Strait Islander community.